Bridging the prohetic legacy through time: A preliminary account on Ahl al-Sunnah wa al-Jama'ah and Perlis state constitution of 1948 - Hassan, Hazman; Ahmad Sabri, Ahmad Zaharuddin Sani; Mohd Othman, Fadlan; Abdul Aziz, Azwira; Basir @ Ahmad, Aminuddin; Othman, Mohd Radzi (2014)
On 1st February 1948, the state of Perlis promulgated her first formally written constitution.Article 5(1) of this constitution declared: ‘The religion of the State shall be the religion of Islam Ahl al-Sunnah wa al-Jama’ah as heretofore professed and practiced in the State’.While other Malaysian states indirectly enshrined Ahl al-Sunnah wa al-Jama’ah or Sunni Islam as the official sect via convention and tradition, Perlis State Constitution of 1948 went further by consolidating the position of Ahl al-Sunnah wa al Jama’ah as inseparable from the religion of the state through the letters of the law.As the Malaysian Federal Constitution is still silent about the official sect in understanding and practicing Islam as a nation, the public debate on this issue has indicated that the Perlis experience now seems has been rather successful in providing legal preservation to the future of Ahl al-Sunnah wa al-Jama’ah in a Malaysian state.Thus this preliminary account tries to emphasize some events and figures in relation to the historic codification of Ahl al-Sunnah wa al-Jama’ahin the Perlis State Constitution of 1948.